Development of Space-Time-Controlled Multi-Stage Pulsed Magnetic Field Forming and Manufacturing Technology at the WHMFC* - Li, Liang; Han, Xiaotao; Cao, Quanliang; Chen, Qi; Lai, Zhipeng; Zhou, Zhongyu; Xiong, Qi; Zhang, Xiao; Li, Xin; Fu, Jiekai; Liu, Yuanhang (Technische Universität Dortmund, 2014)
In November 2011, the Project of Basic Research of Forming by Space-Time-Controlled Multi-Stage Pulsed Magnetic Field (Stic-Must-PMF) was supported by the National Basic Research Program of China (973 Project, 2011.11-2016.08). It is aimed at achieving breakthroughs in manufacturing technology to solve current problems in forming largescale and complex sheet and tube parts and components, imposed by the limitations of existing equipment and materials forming properties. The objective of our research group focuses on the design principles and structural layout optimization of Stic-Must-PMF facility. And this paper will report the development of Stic-Must-PMF forming and manufacturing technology at the Wuhan National High Magnetic Field Center (WHMFC) including numerical modeling, experimental setup and experimental studies.
Keywords: electromagnetic forming; finite element method; space-time-controlled; 620; 670